Maintaining genetic stability in a control flock of South African Merino sheep - Heydenrych, H.J.; Vosolo, L.P.; Plessis, J.J. du; Meissenheimer, D.J.B. (1984)
A genetic control flock of Merino sheep consisting of 160 ewes and 16 rams was established in 1969 at the Tygerhoek Experimental Farm near Riviersonderend in the South Western Districts of South Africa. In 1976 it was extended to 200 ewes and 20 rams. Ewes are replaced by their second ewe lamb when it reaches joining age and rams are replaced yearly, by a randomly chosen son. Four body-mass and six wool traits of the off-spring are measured every year, Random discrepancies between the means of whole progeny and replacement groups for the measured characters varied from 0 to 6,2 % over a period of 11 years, but was on average, roughly zero for individual traits over all years. Regression equations for trait means on time showed the following total changes from 1971 to 1981: Birth mass -23,4 %, 42-day body mass -8.9 %, 120-day body mass + 4,7 %, 18-rnonth body mass -1,7 %, greasy fleece mass -11,1 %, percentage clean yield + 1,5 %, clean fleece mass -9,8 %, staple length + 1,0 %, crimp frequency -1,5 % and fibre diameter -0,7 %. Only the regression for birth mass (-0.096±0,01 kg/year) was significant. That the changes with regard to 42-day body mass and greasy and clean fleece mass were not caused by genetic drift, is indicated by the low increase in inbreeding of only 1,2 % over the 11 years covered in this report. It is concluded that genetic stability can be maintained in a Merino control flock of this size under practical conditions.